Sintering effect on mechanical properties of enamel derived and synthetic hydroxyapatite-zirconia composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
In this study, sintering of synthetic and enamel derived Hydroxyapatite-zirconia (HA-Zr) (doped with 3 mol %Y2O3) composite powder compacts was studied. HA, one of the bioactive ceramics has experienced the widest clinical use because it is the main constituent of hard tissue such as bone, enamel, and dentine and has proven to be highly biocompatible in in vitro and in vivo experiments. Unfortunately, HA is a ceramic and therefore inherently brittle with a fracture toughness comparable to that of osteoporitic bone. The enamel HA powder used in this study was derived from freshly extracted human teeth. After calcination at 850degreesC, only the enamel part of the teeth was used. The compacts consisting of 5 and 10 wt % Zr were sintered at 1200 and 1300degreesC. The density, microhardness and compression strength tests were performed. The average densities for enamel derived HA-Zr and synthetic HA-Zr composites were found as 2.871 +/- 0.177 g/cm(3) and 2,993 +/- 0.066 g/cm(3), respectively. The average compression strength values for enamel derived HA-Zr and synthetic HA-Zr composites were found as 82.45 +/- 27 MPa and 30.31 +/- 18 MPa, respectively. The average values of Vickers microhardness for enamel derived HA-Zr and synthetic HA-Zr composites were found to be 335 +/- 79 HV (kg/mm) and 399 +/- 110 HV (kg/mm(2)), respectively.
Keywords: hydroxyapatite; zirconia; enamel; composite; mechanical properties; REINFORCED HYDROXYAPATITE; BIOMEDICAL APPLICATIONS; BIOGLASS